PENDIDIKAN AGAMA ISLAM SEBAGAI BASIC KEDISIPLINAN: Studi Fenomenologi di SMP Negeri 3 Lembah Melintang Pasaman Barat - Khairunnas, Khairunnas; Ritonga, Mahyudin; Lahmi, Ahmad (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2021)
Educational institutions have different rules from each other, discipline is needed to equalize perceptions and actions in institutions where discipline is applied, in reality many rules have been agreed among all school communities but compliance is not realized as it should be. The existence of Islamic religious education is seen as having a role in realizing the discipline of learners, in line with this research aims to see the phenomenon of how Islamic religious education is used as the basis for the application of discipline in schools. This research is designed with qualitative approach, the data source includes Islamic religious education teachers, purposively selected learners. Research data is collected through observations, interviews and documentation studies. Research data is analyzed through interactive. The results prove that Islamic religious education in SMP Negeri contains a fairly complex disciplinary value, even all disciplines agreed at SMP Negeri 3 Lembah Melintang are substantively contained in PAI. PAI as a basic discipline is seen in the practice of Islamic values among teachers and students.